Effect of PCSK9 on atherosclerotic cardiovascular diseases and its mechanisms: Focus on immune regulation - Ma, Minglu; Hou, Chang; Liu, Jian (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis is a basic pathological characteristic of many cardiovascular diseases, and if not effectively treated, patients with such disease may progress to atherosclerotic cardiovascular diseases (ASCVDs) and even heart failure. The level of plasma proprotein convertase subtilisin/kexin type 9 (PCSK9) is significantly higher in patients with ASCVDs than in the healthy population, suggesting that it may be a promising new target for the treatment of ASCVDs. PCSK9 produced by the liver and released into circulation inhibits the clearance of plasma low-density lipoprotein-cholesterol (LDL-C), mainly by downregulating the level of LDL-C receptor (LDLR) on the surface of hepatocytes, leading to upregulated LDL-C in plasma. Numerous studies have revealed that PCSK9 may cause poor prognosis of ASCVDs by activating the inflammatory response and promoting the process of thrombosis and cell death independent of its lipid-regulatory function, yet the underlying mechanisms still need to be further clarified. In patients with ASCVDs who are intolerant to statins or whose plasma LDL-C levels fail to descend to the target value after treatment with high-dose statins, PCSK9 inhibitors often improve their clinical outcomes. Here, we summarize the biological characteristics and functional mechanisms of PCSK9, highlighting its immunoregulatory function. We also discuss the effects of PCSK9 on common ASCVDs.